How accurate is the urine dipstick test for diagnosing urinary tract infection? - Paydaş Hataysal, Esra; Saraçlıgil, Beyza; Türk Dağı, Hatice; Vatansev, Hüsamettin (The European Research Journal, 2019)
Objectives: Urine dipstick is the first step laboratory test to diagnose a urinary tract infection (UTI) which is a common infectious disease diagnosed in the laboratories. Early treatment of UTI is very important in order to prevent long-term complications. The gold standard to diagnose UTI is urine culture so there are a number of unnecessary urine culture requests. However, urine culture results are not available earlier than 24-36 hours. Besides, urine culture is expensive and causes time-consuming of treatment. Our aim in this study was to compare urine leukocyte esterase test and nitrite test of urine dipstick with urine culture to determinate the sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV). Methods: Urine culture results and urine dipstick test results of patients who admitted to Selçuk University Hospital between May 2016 and May 2017 were collected retrospectively. The study included 11.169 patients and 3299 of them have positive urine cultures. Results: In total, 3299 (29.5%) patients have positive urine culture. Out of these culture positive samples, positive dipstick results’ ratios for leukocyte esterase and nitrite were 82.8% (n = 2733) and 22.4% (n = 774). Leukocyte esterase had 82.8% sensitivity and 68.1% specificity, with PPVs and NPVs of 52.1% and 90.5%, respectively. Conclusions: The NPVs are found significantly higher than PPVs and it shows that urinary dipstick is more reliable to exclude disease than to diagnose the disease. Clinicians should not order urine culture from all patients without ant clinic signs.